Pembangunan Kota Berkelanjutan: Belajar dari Curitiba - Rosyidie, Arief (Journal of Regional and City Planning, 2004)
Urban areas, particularly metropolitan areas, throughout the world are increasingly faced environmental degradations (pollution squatter settlements, wastes) as well as economic and social problems (unemployment, violence, street children). Local governments, particularly in developing countries, have implemented various programs aimed to improve the quality of city in Brazilia, faced the same problems with other cities. The local government of Curitiba has been implementing various program in order to create a sustainable cities. The process of redesigning Curitiba focused on the transportation system in the city. Integration of traffic management, public transportation and land-use planning have successfully minimized the downtown traffic. It's also encouraging social interactions by providing more leisure areas (parks, open spaces, etc) and pedestrian zones in the city centre. Furthermore, the plan also encourages the use of public transport and recycling system in order to achieve an environmentally healthy city. Sustainable Curitiba has been achieved since it was supported by the strong leader, who has a long experience and a vision in urban planning, as well as supported by social capital of community participation. Curitiba now is the world's showcase ecocities and ecological capital of Brazil. Urban managers and planners from all over the world learn from the successfull of Curitiba's sustainable development.